Yoruba vocal music - Beier, Ulli (International Library of African Music, 1956)
Much more attention has so far been paid to the famous instrumental music of the Yorubas than to their vocal music. The fame of the “Dundun” drum, the famous talking instrument, has probably overshadowed Yoruba singing. Yet there is an immensely rich field of study even here. There is no occasion in Yoruba life that is not accompanied by songs. Birth, marriage and funeral are all occasions for lyrical songs of great beauty. Everyday life is also accompanied by a great deal of impromptu singing, a kind of musical thinking, in which the singer puts everything to a tune, which happens to pass through his head. The Yorubas are indeed a poetic nation, because every person has his own praise songs, by which he will be greeted on all important occasions. Professional singers are able to recite these oriki (e.g. praise songs) of every important man in the town and those of his ancestors as well. In the case of a king, the praise singer must remember the oriki of all the kings from the beginning of the town.
Keywords: Yoruba (African people); Music; Sacred music; Vocal music; Ethnomusicology; African Music; Religious Aspects; Yoruba Art; Nigeria